A novel risk score to predict deep vein thrombosis after spontaneous intracerebral hemorrhage - Ji, Ruijun; Wang, Linlin; Liu, Xinyu; Liu, Yanfang; Wang, Dandan; Wang, Wenjuan; Zhang, Runhua; Jiang, Ruixuan; Jia, Jiaokun; Feng, Hao; Ding, Zeyu; Ju, Yi; et al. (Frontiers in Neurology, 2022)
Background and purpose: Studies showed that patients with hemorrhagic stroke are at higher risk of developing deep vein thrombosis (DVT) than those with ischemic stroke. We aimed to develop a risk score (intracerebral hemorrhage associated deep vein thrombosis score, ICH-DVT) for predicting in-hospital DVT after ICH. Methods: The ICH-DVT was developed based on the Beijing Registration of Intracerebral Hemorrhage, in which eligible patients were randomly divided into derivation (60%) and internal validation cohort (40%). External validation was performed using the iMCAS study (In-hospital Medical Complication after Acute Stroke). Independent predictors of in-hospital DVT after ICH were obtained using multivariable logistic regression and β-coefficients were used to generate scoring system of the ICH-DVT. The area under the receiver operating characteristic curve (AUROC) and the Hosmer-Lemeshow goodness-of-fit test was used to assess model discrimination and calibration. Results: The overall in-hospital DVT after ICH was 6.3%，6.0%, and 5.7% in the derivation (n=1309), internal (n=655) and external (n=314) validation cohorts, respectively. A 31-point ICH-DVT was developed from the set of independent predictors including age, hematoma volume, subarachnoid extension, pneumonia, gastrointestinal bleeding and length of hospitalization. The ICH-DVT showed good discrimination (AUROC) in the derivation (0.81; 95% CI=0.79-0.83), internal (0.83, 95% CI=0.80-0.86) and external (0.88; 95% CI=0.84-0.92) validation cohorts. The ICH-DVT was well calibrated (Hosmer-Lemeshow test) in the derivation (P=0.53), internal (P=0.38) and external (P=0.06) validation cohorts. Conclusion: The ICH-DVT is a valid grading scale for predicting in-hospital DVT after ICH, which would be useful for personalized care and clinical trial in ICH.